New non degenerate invariant measures for the Benjamin–Ono equation - Tzvetkov, Nikolay (Comptes Rendus. Mathématique, 2024)
We show that the recent work by Gérard–Kappeler–Topalov can be used in order to construct new non degenerate invariant measures for the Benjamin–Ono equation on the Sobolev spaces $H^s$, $s>-1/2$.